DETECTION OF KI-67, BCL-2, TERMINALLY APOPTOTIC CELLS (TUNEL ASSAY), CD34 AND VEGF IN AMELOBLASTOMA - Younis, Wasan Hamdi; Hussein, Alaa G.; Garib, Balkees T. (European Scientific Journal, ESJ, 2014)
Background: Ameloblastoma is a benign local aggressiveness odontogenic tumor that has great tendency to recur. Aims: characterize the staining profiles of various markers in ameloblastoma. Materials and methods: immunohistochemical analysis of Ki-67, Bcl2, CD34 and VEGF and TUNEL assay were performed in 50 ameloblastomas. Mann- Whiteny and Pearson’s correlation applied for analysis. P < 0.05 was considered statistically significant. Results: The outer odontogenic epithelial cells of ameloblastoma had low Ki-67 labeling index (3.66±4.39) that is significant differed among its subtypes, and high Bcl2 expression in all variants (74.39%) and lining cells of unicystic ameloblastoma. On the other hand, inner odontogenic epithelial cells of ameloblastoma had low apoptotic index mean (3.5%), nevertheless high values were observed in acanthomatous (7.76%) and follicular (6.1%) subtypes. The mean count of new micro-vessels was (22.4±25.54). They were predominantly round-shaped small-sized vessels. VEGF was highly expressed in the outer cells, and correlated with microvessels’ count (r=0.35). VEGF expression did not relate to histological variation. Conclusions: Ameloblastomas have high-strong expression for both Bcl2 and VEGF in outer tumor cells, and aberrant stromal neo-vascularization, but Ki67 expression significantly differed among their variants. Unicystic ameloblastoma should be considered with caution, their lining cells showed features of aggressiveness. It is recommended to evaluate Bcl2 and MvD to predict aggressiveness and VEGF to evaluate potential tumor survival and growth that may poses a possible benefit in treatment planes.